Ferns (Pteridophyta) Diversity in West Kalimantan: A Literature-Based Study - Rifki; Syamswisna; Audiva Azhta Prameswari; Irvan Ariyansyah; Putri Anggini; Angel Acum Diarsih (Universitas Cokroaminoto Palopo, 2024)
Indonesia is a tropical country that has a diversity of flora and fauna that must be preserved and developed, one of which is ferns. Ferns can grow well in open ground. With sufficient sunlight, acidity (pH) of 3.5–6.5, and temperature of 21-27°C, ferns can grow after forest fires or forests covered by tree canopies. West Kalimantan has a humid tropical climate, diverse habitats, nutrient-rich soil, dense forest canopy, lack of human disturbance, and complex natural ecological processes. Ferns grow and live in a variety of species in the forests of West Kalimantan. The approach used is a literature study, namely looking for primary sources or literature in the form of national and international journals in the previous decade (2014-2024). There are 16 families with 34 species. The most commonly found species come from the Polypodiaceae family. This article can be used as a source of information to support additional research on ferns.